2022
DOI: 10.1007/978-3-031-17551-0_25
|View full text |Cite
|
Sign up to set email alerts
|

An Intrusion Detection System Based on Deep Belief Networks

Abstract: The rapid growth of connected devices has led to the proliferation of novel cyber-security threats known as zero-day attacks. Traditional behaviour-based Intrusion Detection Systems (IDSs) rely on Deep Neural Networks (DNNs) to detect these attacks. The quality of the dataset used to train the DNNs plays a critical role in the detection performance, with underrepresented samples causing poor performances. In this paper, we develop and evaluate the performance of Deep Belief Networks (DBNs) on detecting cyber-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This section reviews recent federated learning strategies for intrusion-detection systems (IDS) and compares them with the approach proposed in this paper. The authors in [ 54 ] employ an architecture very similar to the one we propose, concluding that utilizing an initially pre-trained model leads to better results. This mirrors the approach we adopt, initiating with a Baseline K-means model that has been pre-trained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This section reviews recent federated learning strategies for intrusion-detection systems (IDS) and compares them with the approach proposed in this paper. The authors in [ 54 ] employ an architecture very similar to the one we propose, concluding that utilizing an initially pre-trained model leads to better results. This mirrors the approach we adopt, initiating with a Baseline K-means model that has been pre-trained.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our work, which formulates the problem as a semi-supervised novelty detection task, they use a Deep Neural Network (DNN) and Deep Belief Network (DBN) for supervised multi-class classification. The work in [ 54 ] might be more suitable for IoT devices with substantial memory and computational capabilities, such as the Raspberry Pi 4, whereas our approach, due to the simplicity of the K-means algorithm compared to a neural network, can be embedded on more constrained devices like the ESP32.…”
Section: Discussionmentioning
confidence: 99%
“…As the intrusion detection system is the main source of security elements in situation awareness, its accuracy directly affects the assessment of network security. It can detect the maliciousness without compromising the security of hosts and networks [32]. This article further combines network intrusion security with security factors, such as devices and applications, to construct a multifactor fusion network security situation assessment scheme, further improving the effectiveness and accuracy of security situation assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The KDD-CUP99 dataset was again used, showing reduced FPs and improved speeds. Belarbi et al [32] proposed a multi-class NIDS based on a deep belief network (DBN) using the CICIDS2017 dataset to train and evaluate performance. The experimental results demonstrated that DBNs can surpass traditional multilayer perceptron classification performance, significantly improving overall recall.…”
Section: B Algorithm-level Mitigation Effortsmentioning
confidence: 99%